Peningkatan Kewirausahaan melalui Pembelajaran dengan Menggunakan Media Budidaya pada Anak Usia Dini di TK Taqifa Bangkinang Kota Tahun 2016 - Rinda Fithriyana (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2016)
Efforts to Boost Entrepreneurship Through Children grow tanampada early childhood / kindergarten Taqifa. Entrepreneurial spirit needs to be owned by anyone, not least children at an early age. Entrepreneurship education is not just to educate potential entrepreneurs or to teach children earning money early, but to grow and develop characters that already exist in children. The purpose of this study was to: find out whether there is any change in habits and behaved child after doing fun activities in farming and increase entrepreneurship spirit early. This study used a qualitative research approach, that is data that contains information in the form of a sentence that gives an overview of all activities of children in this research activity. The hypothesis could be given of this research is the entrepreneurship activity through cultivation can foster the entrepreneurial spirit in early childhood educator / TK Taqifa. Planting an entrepreneurial spirit from an early age children make children have a strong mental effort, a sense of responsibility and self-reliant attitude.